Disentangling the Wage Impacts of Offshoring on a Developing Country: Theory and Policy - Subhayu Bandyopadhyay; Arnab K. Basu; Nancy Chau; Devashish Mitra (Institute for the Study of Labor (IZA), 2016)
The various channels through which a reduction in the cost of offshoring can improve wages in a developed country are by now well understood. But does a similar reduction in the offshoring cost also benefit workers in the world's factories in developing countries? Using a parsimonious two-country model of offshoring we find very nuanced results. These include cases where wages monotonically improve or worsen as well as those where wages exhibit an inverted U-shaped relationship in response to parametric reductions in the cost of offshoring. We identify qualitative conditions under which wages and welfare increase or decrease in the developing world as a result of a reduction in offshoring costs. Since global welfare always rises with an improvement in offshoring technology, we find that there is a role for a wage tax or a minimum wage in the developing country. We derive the optimal levels of such policies.
Keywords: F11; F13; F16; F66; O19; O24; 330; wages; international offshoring; wage tax; minimum wage